2018
DOI: 10.1111/acem.13358
|View full text |Cite
|
Sign up to set email alerts
|

Homelessness and Emergency Medicine: A Review of the Literature

Abstract: Homelessness may be underrecognized in the ED setting. Homeless ED patients have distinct care needs and patterns of ED utilization that are unmet by the current disease-oriented and episodic models of emergency medicine. More research is needed to determine the prevalence and characteristics of homelessness in the ED and to develop evidence-based treatment strategies in caring for this vulnerable population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
89
0
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 106 publications
(103 citation statements)
references
References 80 publications
2
89
0
7
Order By: Relevance
“…Australian research mapping the spatial dynamics of homelessness found that inner city and remote (in particular northern and central Australian) local government areas had the highest share of homelessness, increasing the likelihood of hospitals in these regions servicing homeless individuals. Therefore while our study also found frequent use of hospital ED services by homeless patients, multiple factors need to be considered by health services wanting to determine local homeless prevalence …”
Section: Discussionmentioning
confidence: 62%
“…Australian research mapping the spatial dynamics of homelessness found that inner city and remote (in particular northern and central Australian) local government areas had the highest share of homelessness, increasing the likelihood of hospitals in these regions servicing homeless individuals. Therefore while our study also found frequent use of hospital ED services by homeless patients, multiple factors need to be considered by health services wanting to determine local homeless prevalence …”
Section: Discussionmentioning
confidence: 62%
“…This study was conducted among a very unique subpopulation of ED patients and did not specifically explore pathways to homelessness. Homelessness plays an oversized role in U.S. EDs, in part due to the ED's role as a medical and social safety net and in part due to the greater than average health needs of people who are homeless . Research spanning multiple localities and types of EDs has found that a disproportionate number of ED patients are homeless .…”
Section: Discussionmentioning
confidence: 99%
“…Homelessness plays an oversized role in U.S. EDs, in part due to the ED's role as a medical and social safety net and in part due to the greater than average health needs of people who are homeless . Research spanning multiple localities and types of EDs has found that a disproportionate number of ED patients are homeless . Other research has found that ED providers struggle to provide optimal care to patients who are homeless, which may lead to provider burnout …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Health policy, material deprivation, inequality, and stigma are implicated in poor health outcomes among emergency department (ED) patients . Researchers have emphasized the role of the social determinants of health, structural racism, gender discrimination, homophobia, and transphobia on the health of ED patients. These topics continue to gain interest and attention as their ties to medical education, clinical care, and population health are elucidated and emphasized.…”
mentioning
confidence: 99%